Pengaruh tingkat pengangguran, inflasi dan negara sasaran terhadap perdagangan Internasional Indonesia - Hodijah, Siti; Simamora, Leonardo (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
The purpose of this study was to determine the effect of unemployment and inflation as well as the reasons for choosing target players in carrying out export activities (international trade). This type of research is quantitative research. The data used are secondary data from Indonesia for the 2001-2020 period. The data is processed using data analysis Vector Autoregression or VAR. The results showed that unemployment had a positive and significant effect on inflation and inflation had no significant effect on unemployment. while exports have a positive and insignificant effect on unemployment. And exports and inflation are insignificant. Â